Corporate Social Responsibility, Capital Intensity, and Tax Aggresiveness: Evidence from Indonesia - Dinda Ayu Laksmi; Niluh Putu Dian Rosalina Handayani Narsa (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2022)
Abstract Many empirical evidences regarding the relationship between Corporate Social Responsibility (CSR) and Tax Aggresiveness (TA) had shown inconsistency, thus, there is a need to reconcile those findings by utilize moderating variables which in turn hopefully will provide a more specific explanation regarding the mechanism behind it. This study aims to obtain empirical evidence related to the relationship between CSR and TA and also the relationship between CSR and TA with capital intensity as a moderator. CSR in this study was measured using the index from Global Reporting Intiatives (GRI) version 4. The sample used in this study was 384 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The data obtained were analyzed using SPSS with multiple linear regression analysis and moderated regression analysis. The results show that CSR is negatively related to TA. Furthermore it is also found that capital intensity has a role as pure moderator variable that can weaken the negative relationship between CSR and TA, or in other words the interaction between CSR and capital intensity tends to cause company to engage in TA